Education on The Use of Herbal Medicines for The Prevention and Treatment of Covid-19 - Evi Sovia; Welly Ratwita; Maman Djamaludin (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
To date, the Coronavirus disease-19 (Covid-19) pandemic still occurs and there has not been found a satisfactory specific treatment to treat Covid-19. Some medicinal plants are known to increase body endurance and are useful for maintaining health during a pandemic. This community service activity aims to provide education in an effort to increase public knowledge about the use of herbal medicines for the prevention and treatment of Covid-19. The method used is a webinar with three presentation materials that are myths and facts about the use of herbal medicines for Covid-19, is it safe to consume herbal medicines and the classification of herbal medicines based on scientific evidence. In this activity, participants were also given a questionnaire to determine the knowledge of the webinar participants about herbal medicine. The results of the questionnaire showed that most of the webinar participants consumed herbal medicines (84%) with the aim of maintaining health. Meanwhile, the most widely consumed type of herbal medicine was jamu (42.8%) and the most widely used medicinal plant was ginger (50.36%). Most of the participants in the webinar (60%) believe in the safety of herbal medicines. In conclusion, public knowledge about the use of herbal medicines and their safety needs to be improved.